The Participation of Religious Organisations and Their Contributions to the Countermeasure of HIV/AIDS in Indonesia - Junaidah Junaidah; Andi Faisal Bakti (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2022)
Several works available on religion and HIV/AIDS indicated that several religious groups in the world, including Indonesia, are still reluctant to be involved in the prevention of HIV/AIDS. However, the involvement of the two largest religious organisations in Indonesia, Nahdlatul Ulama (NU) and Moluccas Protestant Church (Gereja Protestan Maluku/GPM) in combating HIV/AIDS for the last ten years deserve to be investigated and studied, as new evidence which refutes the above studies. The result of this study shows, first, the involvement of NU and GPM in the prevention of HIV/AIDS showed the potential of religious organisations in health development, particularly as a progressive strength in the fight against pandemics such as HIV/AIDS. Second, the most fundamental forms of involvement are changing religious views about HIV/AIDS as a cursed disease into a disaster or a test that requires patience. NU and GPM also organise social activities, public education, and policy advocacy for HIV/AIDS programs. Third, although this article has not been able to present the decrease of HIV/AIDS prevalence in Indonesia as a result of religious organisations involvement such as NU and GPM, however, at least there have been some contributions from both organisations toward the decrease of negative stigmatisation to people living with HIV/AIDS.